Pendekatan Neo-Ekspressionisme dalam fotografi - Alice, ak. Lanting. (Universiti Malaysia Sarawak (UNIMAS), 2006)
Neo-Expressionism plays an important role in the development of photography and was discussed in this research. It's in the form of expression of emotion or discontent towards environmental issues; destruction and discrimination, as a result of the society's attitude that gives priority to profitability. Usages of poker cards symbols are to convey the hidden meaning and messages.